Solid-State Metathetic Synthesis and Photoluminescence of Calcium Tungstate Particles Assisted by Cyclic Microwave Irradiation - Oh, Won-Chun; Yeon Park, Chong; Won Jeon, Jeong; Sung Lim, Chang (Asian Journal of Chemistry, 2012)
A solid-state metathetic (SSM) route assisted by cyclic microwave irradiation was used to synthesize calcium tungstate (CaWO4) particles. Well crystallized CaWO4 particles were formed at 600 ºC for 3 h, showing a fine and homogeneous morphology with sizes of 1-2 μm. The characteristics of the solid-state metathetic reaction of the CaWO4 particles were examined in detail based on the exothermic reaction. The obtained CaWO4 particles were characterized by X-ray diffraction, Fourier transform infrared spectroscopy and scanning electron microscopy. The optical properties were examined by photoluminescence emission and Raman spectroscopy.